Beliefs about school mathematics vs. university mathematics and beliefs about teaching and learning in different contexts of students’ achievement - Safrudiannur Safrudiannur; P.M. Labulan; Suriaty Suriaty; Benjamin Rott (Universitas Islam Negeri (UIN) Mataram, 2021)
[English]: This quantitative study with n = 206 participants (mathematics pre-service teachers from Indonesia) investigates the effect of two factors on pre-service teachers’ beliefs: (1) contexts related to students’ achievement as well as (2) the differences between school mathematics and university mathematics. The results of this quantitative study show that the participants (1) have different beliefs about teaching and learning of mathematics in different contexts of students’ achievement (a class dominated by high-achieving students vs. a class dominated by low-achieving students) and (2) have different beliefs about school mathematics and university mathematics. Interestingly, compared to their beliefs about school mathematics, the pre-service teachers’ beliefs about university mathematics correlate better with their beliefs about teaching and learning in different contexts of students’ achievement. The implication of the better correlations for the pre-service teacher education are further discussed. [Bahasa]: Penelitian kuantitatif dengan 206 calon guru matematika ini bertujuan untuk menginvestigasi efek dari dua faktor yang mempengaruhi keyakinan para calon guru: (1) konteks yang berhubungan dengan capaian siswa dan (2) perbedaan karakteristik antara matematika sekolah dan matematika universitas. Hasil penelitian menunjukkan bahwa para calon guru tersebut (1) memiliki keyakinan yang berbeda tentang bagaimana mengajar dan belajar matematika di dalam konteks yang berbeda, yaitu antara kelas yang didominasi oleh siswa-siswa capaian tinggi dan kelas yang didominasi oleh siswa-siswa capaian rendah, dan (2) memiliki keyakinan yang berbeda antara matematika sekolah dan matematika universitas. Menariknya, jika dibandingkan dengan keyakinan tentang matematika sekolah, keyakinan para calon guru tentang matematika universitas ternyata lebih baik korelasinya terhadap keyakinan mereka tentang bagaimana mengajar dan belajar di dua konteks kelas tersebut. Selanjutnya, artikel ini akan mendiskusikan implikasi dari korelasi yang lebih baik tersebut terhadap pendidikan para calon guru matematika.